2015
DOI: 10.1016/j.mehy.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Relative fascicle excursion effects on dynamic strength generation during gait in children with cerebral palsy

Abstract: Evaluation of muscle structure gives us a better understanding of how muscles contribute to force generation which is significantly altered in children with cerebral palsy (CP). While most muscle structure parameters have shown to be significantly correlated to different expressions of strength development in children with CP and typically developing (TD) children, conflicting results are found for muscle fascicle length. Muscle fascicle length determines muscle excursion and velocity, and contrary to what mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Based on the clinical experience, motor dysfunctions may be influenced more by limitations related to mechanical factors in soft tissues than to neurological factors in central command disorders as children with CP have grown up to be youths and adults. Fascicle length is especially important when analyzing muscle architecture because it is highly related to secondary musculoskeletal contracture development, which can severely limit the initial length of muscle contraction and excursion[ 9 , 28 , 40 , 46 , 47 ]. In this study, we show that the fascicle length in the affected calf was shorter than that observed in both TD peers and the unaffected side of children with hemiplegic CP.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the clinical experience, motor dysfunctions may be influenced more by limitations related to mechanical factors in soft tissues than to neurological factors in central command disorders as children with CP have grown up to be youths and adults. Fascicle length is especially important when analyzing muscle architecture because it is highly related to secondary musculoskeletal contracture development, which can severely limit the initial length of muscle contraction and excursion[ 9 , 28 , 40 , 46 , 47 ]. In this study, we show that the fascicle length in the affected calf was shorter than that observed in both TD peers and the unaffected side of children with hemiplegic CP.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative theory to explain the higher RTD is that girls with GJH use a more optimal joint position for rapid force generation in the isometric knee flexion test compared to NGJH girls, or in other words girls with GJH operate closer to the optimal region of the length-tension curve than NGJH girls. An association between relative muscle length and rate of force development in children with cerebral palsy was suggested recently as a possible underlying mechanism for understanding why these children have a reduced range of motion and reduced rate of force development compared to typically developing children [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 While acknowledging the complex, multifactorial nature of crouch gait pathogenesis, an attempt should be made to treat as many of the existing causes as possible as part of a tailored approach. 20 Even for reducible deformities and in the absence of transverse or frontal plane abnormalities, nonsurgical treatments, such as physiotherapy and antigravity muscle strengthening, 24,25 together with spasticity management and orthotic adjustment 26 seem insufficient. 27,28 Among the surgical procedures used to correct crouch gait, distal hamstring lengthening (HSL) has traditionally been used to improve KE.…”
Section: Introductionmentioning
confidence: 99%